Modellierung des Kreditrisikos im Einwertpapierfall - Heinz Cremers; Jens Walzner (Frankfurt School of Finance & Management, 2009)
The current financial market crisis has impressively demonstrated the importance of an effective credit risk management for financial institutions. At the same time, the use and the valuation of credit derivatives has been widely criticised as a result of the crisis. Over the past decade, credit derivatives emerged as an important part of credit risk management as these offer a broad range of possibilities to reduce credit risk through active credit portfolio management. This has represented a quantum leap in the further development of credit risk management. Credit risk management, without using credit derivatives, no longer seems to be an appropriate alternative. However, correct valuation of these derivatives is still challenging. The crisis has demonstrated that the issue is less about using credit derivatives than about developing valid valuation techniques. A sound understanding of already existing credit pricing models is necessary for such a development. These models are the key focus of this working paper.
urn:nbn:de:101:1-20090826287
Keywords: C22; G12; G21; G32; 330; Credit risk pricing models; asset-based models; asset-value models; structural models; intensity-based models; reduced-form models; credit derivatives; credit default swap; pricing; valuation; default spread; risk management; credit portfolio management